Legal protection of investors, corporate governance, and the cost of equity capital - Chen, Kevin C.W.; Chen, Zhihong; Wei, K.C. John (Journal of Corporate Finance, 2009)
This study examines the effect of firm-level corporate governance on the cost of equity capital in emerging markets and how the effect is influenced by country-level legal protection of investors. We find that firm-level corporate governance has a significantly negative effect on the cost of equity capital in these markets. In addition, this corporate governance effect is more pronounced in countries that provide relatively poor legal protection. Thus, in emerging markets, firm-level corporate governance and country-level shareholder protection seem to be substitutes for each other in reducing the cost of equity. Our results are consistent with the finding from McKinsey's surveys that institutional investors are willing to pay a higher premium for shares in firms with good corporate governance, especially when the firms are in countries where the legal protection of investors is weak.